The request of the chairman of the mahalla citizens’ meeting is an effective form of public control - Bafaev Shukhrat Gafurovich (The American Journal of Political Science Law and Criminology, 2025)
The article analyzes, within the framework of the Law of the Republic of Uzbekistan "On Public control", the issues of making requests to representative bodies of local government by the chairman of the mahalla citizens' meeting, analyzes the legal nature of the request, the difference between the request and the parliamentary request, as well as the request related to obtaining the necessary information related to the activities of the citizens' meeting. The request of the chairman of the сitizens' Assembly will serve to implement the concept of developing a free and open civil society in the country.